2013
DOI: 10.1021/bc3004815
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Antibodies to Gold Nanorods through Fc Portion: Synthesis and Molecular Specific Imaging

Abstract: Anisotropic gold nanorods provide a convenient combination of properties, such as tunability of plasmon resonances and strong extinction cross-sections in the near-infrared to red spectral region. These properties have created significant interest in the development of antibody conjugation methods for synthesis of targeted nanorods for a number of biomedical applications, including molecular specific imaging and therapy. Previously published conjugation approaches have achieved molecular specificity. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 93 publications
3
71
0
Order By: Relevance
“…The A.R decreased during the conjugation procedure. 22 With NBP amplification, shown in Fig. 8, both frequencies were changed when the concentrations of CAP were 0.5 ppm.…”
Section: Signal Amplification Of Qcm-immunosensormentioning
confidence: 98%
“…The A.R decreased during the conjugation procedure. 22 With NBP amplification, shown in Fig. 8, both frequencies were changed when the concentrations of CAP were 0.5 ppm.…”
Section: Signal Amplification Of Qcm-immunosensormentioning
confidence: 98%
“…Examples from these reviews include cell imaging using nanorods [9] and nanoshells [21]. Instruments based on hyperspectral darkfield have enabled quantitative molecular imaging [22] and spectral multiplexing [7], using functionalized nanoparticles where an antibody conjugate provides molecular specificity [4,23]. These instruments are even capable of detecting plamonic shifts due to coupling which can then be used to provide additional spatial information [24][25][26].…”
Section: Darkfield Microspectroscopymentioning
confidence: 99%
“…There have been a number of reviews that focus on development and synthesis of nanoparticle structures [1][2][3][4][5], as well specific applications for optical imaging [6]. However, there has been little attention paid to determining optimal methods for discriminating the presence and concentration of nanoparticles as optical contrast agents.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In the past studies, Eustis and ElSayed investigated the relative intensity of the emission from AuNRs of various aspect ratios and theoretical treatments were also carried out. 4 After that, Tcherniak et al reported one-photon luminescence of gold nanospheres and nanorods using single particle spectroscopy and presented a mechanism describing one-photon luminescence.…”
Section: Introductionmentioning
confidence: 99%